Perencanaan Cell Plan Di Kecamatan Bukit Raya Kota Pekanbaru Menggunakan Software Mapinfo - Lubis, Ahmad Sofyan; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
LTE technology is a technological evolution of the UMTS (Universal Mobile Telecommunication System) on the three-generation (3G). Mobile telecommunications service providers have the opportunity to use technology through frequency refarming. Before applying the LTE technology, cell planning based on capacity and coverage need calculated in orde to calculated the number of site eNodeB. This research aims to provide of placement site and the number of sites required for the implementation of eNodeB of frequency 1850MHz. Calculation the number of site eNodeB is based on capacity dimensioning and coverage planning. The results showed the number of sites required in the Sub-district Bukit Raya Pekanbaru is 31 site.Keyword: LTE, Cell Planning, Mapinfo, Capacity Planning, Coverage Planning.